KERAGAMAN PRODUKTIVITAS KOMODITAS KEDELAI PADA BERBAGAI SKENARIO PERUBAHAN IKLIM MENGGUNAKAN MODEL IKLIM DAN PERTANIAN - . Perdinan; I Putu Santikayasa (Institut Pertanian Bogor, 2006)
The need of soybean in Indonesia grows from time to time. Now, Indonesia imports at about 1,1 milion ton/ha yearly. This condition indicates that the need of soybean in Indonesia can be a serious problem of agricultural sector in the future. Furthermore, the climate change issue as a result of human activity used a large amount of fosil fuel will derive a new problem for agricultural sector which requires a better strategy of anticipation. This point out the important of information in order to estimate the potential of soybean's yield in Indoensia in the future. In general, this research is designed to identify the evidence of climate change and to learn the impact of the climate change scenarios on the future of soybean's yield in Bandung district. For this purpose, literature study and analysis of global circulation model (data) data are applied for identifying the occurrence of climate change. Then, the impact analysis of these scenarios on soybean's yield is conducted by using climate and agricultural simulation model, which consist of statistic and mechanistic models. Analysis of the earth surface mean temperature shows the increasing of global air temperature has been started since 19's century with the occurence of increasing temperature from about -0.4 °C to about 0.1 °C in the year of 1940's. Then, the occurence of climate change in Indonesia can be identified using monthly rainfall data for a certain period. Previous study, which has been conducted by Kaimuddin (2000) shows the changing of rainfall pattern in Indonesia. Additionally, analysis on Global Circulation Model (GCM) data for various climate change scenarios reveal the evidence of rainfall and temperature changing variability in percentage for each model in year 2020, 2050 and 2080. The highest value of A2 scenario in come from NIESS, meanwhile for B2 scenario is GFDL. Then, the minimum value is mostly gained from ECHAM model. Moreover, the result of simulation using maximum and minimum value from those scenario for year 2020 decrease in almost of the whole area of Bandung.